The anxiety in English for foreign language speaking class: the case of university students in Lampung context - Septiawan, Habi; Setiyadi, Bambang; Mahpul, Mahpul; Sukirlan, Muhammad; Nisa, Khairun (Intelektual Pustaka Media Utama, 2025)
To date there have been a lot of currently emerging studies focusing on English speaking anxiety experienced by Indonesian university students. Nevertheless, particularly the studies have not investigated university students in Lampung region as the new context. This study aims to describe the level, attitude and perception, and the causes of speaking anxiety in English among university students in the Lampung context. Descriptive research combining quantitative and qualitative approach was performed to conduct this study. 64 new state university students from the English department were involved as participants in this study. A questionnaire and interview form related to speaking anxiety were used to collect the data whereby quantitative data was analyzed by using descriptive statistics while qualitative data was analyzed via content analysis. Results of this study showed that students experienced low anxiety level when speaking English as a foreign language, but mostly they provided the perception that speaking ability was a trigger for anxiety. Even though students' positive attitude towards English used in the classroom was reflected, their speaking skill in English was negative. Additionally, some main sources such as the limited of vocabulary, self-confident, and speaking opportunity were the causes of speaking anxiety.